Analysis of risk factors of hypertension: a cross-sectional study in a rural area - Srinivas, H. D. (International Journal of Research in Medical Sciences, 2024)
Background: Hypertension (high blood pressure) is when the pressure in your blood vessels is too high (140/90 mmHg or higher). It is common but can be serious if not treated. Methods: The present study was conducted at medicine department of Adichunchanagiri Institute of Medical Sciences, Mandya from February to July 2023. Total 100 study subjects in the age group of 30–60 years were included by simple random sampling technique in the present study. Pre-designed, pre-tested proforma was used to collect data regarding demographic characteristics and different risk factors i.e. smoking and alcoholism through house-to-house visits. Results: In the present study the overall prevalence of hypertension was found to be 18%. Similar findings have also been reported in other studies. Comparable prevalence (15%) was found in the study conducted at squatter settlement of Karachi (Pakistan). Similar prevalence of hypertension (16.9%) has also been reported in the study conducted among labour population of Gujarat. Conclusions: Cardiovascular risk factors and lifestyle behaviors are amenable to modification and may therefore be relevant targets in the prevention of hypertension. For some modifiable risk factors, it is unclear whether they are causally related to hypertension. This study found that, BMI, alcohol dependence, insomnia, and educational level are causal risk factors of hypertension. This improved understanding of the pathophysiology of hypertension can be used to identify additional targets for the prevention of hypertension and its association diseases.